A Review of Micro-Hydro Power Plant Technology and its Socio-Economic Impact on Rural Electrification in Indonesia - Hamzah Al Imran; Dara Vann; Ravi Dara (Journal of Multidisciplinary Sustainability Asean, 2025)
Background: Access to electricity in rural areas of Indonesia remains limited, leading to socio-economic challenges such as low productivity, limited education opportunities, and inadequate healthcare services. Micro-hydro power plants (MHPP) have emerged as a promising solution to support rural electrification, offering renewable, decentralized energy sources suitable for remote communities. Objective: This study aims to review the development and application of micro-hydro power plant technology in Indonesia, analyzing its technical characteristics and evaluating its socio-economic impacts on rural communities. Methodology: A systematic literature review was conducted, encompassing peer-reviewed articles, government reports, and case studies from various rural regions in Indonesia. The analysis focused on technical specifications, implementation strategies, community involvement, and socio-economic outcomes associated with micro-hydro projects. Results: Findings indicate that MHPP technology in Indonesia has demonstrated reliable energy generation with capacities ranging from 5 kW to 100 kW, suitable for small communities. Socio-economic benefits include increased household income, improved educational access, enhanced local business development, and strengthened community cohesion. However, challenges such as high initial investment, technical maintenance requirements, and limited technical expertise in rural areas have constrained widespread adoption. Community participation and government support were identified as critical factors for project sustainability. Conclusion: Micro-hydro power plants present an effective approach to rural electrification in Indonesia, with significant socio-economic benefits when supported by local engagement and institutional frameworks. Future policies should focus on reducing technical and financial barriers to maximize the positive impact of MHPP on rural development.